Social Media Marketing and Purchase Decisions: The Mediating Role of Electronic Word of Mouth (E-WOM) Evidence from Dimsumbite, Ternate City - Nisadiayanah, Nadia; Hidayanti, E Ida; Laela, Laela (International Journal of Business, Law, and Education, 2026)
This study aims to analyze the influence of social media marketing on purchase decisions mediated by Electronic Word of Mouth (E-WOM) among Dimsumbite consumers in Ternate City. A quantitative approach was applied using purposive sampling to obtain respondents who had purchased Dimsumbite products and used Instagram or TikTok. Data were analyzed using Structural Equation Modelling–Partial Least Square (SEM-PLS). The results reveal that (1) social media marketing has a positive and significant effect on purchase decisions; (2) social media marketing has a positive and significant effect on Electronic Word of Mouth; (3) Electronic Word of Mouth has a positive and significant effect on purchase decisions; and (4) Electronic Word of Mouth partially mediates the relationship between social media marketing and purchase decisions. These findings indicate that the better the social media marketing strategy implemented by Dimsumbite, the greater the likelihood that consumers will share positive online reviews, which ultimately increases purchase decisions.